Psychotherapy with a 3-Year-Old Child: The Role of Play in the Unfolding Process - Salcuni, Silvia; Di Riso, Daniela; Mabilia, Diana; Lis, Adriana (Frontiers in Psychology, 2017)
Few studies have investigated the outcomes and process of psychodynamic psychotherapies with children. Among the limited number of studies, some only paid attention to play and verbal production, as they are fundamental aspects in assessing the psychotherapy process. This paper focuses on an empirical investigation of a three-year, once-a-week psychodynamic psychotherapy carried out with a 3–year-old girl. A process-outcome design was implemented to evaluate play and verbal discourse in in the initial, middle and final parts of 30 psychotherapy sessions. Repeated measurements of standardized play categories (the Play Category System and the Affect in Play Scale—Preschool version) and verbal discourse (Verbal Production) were analysed. To increase the clinical validity of the study, data from the assessment phase and vignettes from the sessions were reported to deepen the patient’s picture during the unfolding therapy process. Parent reports before and after the therapy were also included. Empirically measured changes in play and verbal production were fundamental in evaluating the young patient’s psychotherapy process. Verbal production and discourse ability progressively increased and took the place of play, which instead became more symbolic. Developmental issues as well as psychotherapy’s influence on the patient’s change, were discussed in relation to the role of play in enhancing the development of verbal dialogue and the expression of the child’s emotions, needs and desires.